The impact of the advertisement on the behavior of the tourist consumer of a sample of customers of tourist agencies in Djelfa - Benzaid, Nadjat (International journal of economic perspectives, 2024)
Through this study, we aim to determine the impact of advertising on the behavior of tourist consumers for a group of travel agencies in Djelfa. A questionnaire was used as a scientific research tool by surveying the opinions of a sample of customers from some travel agencies in the Djelfa province. We found that advertising, through its various means and characteristics, has a significant impact on tourist consumer behavior. In conclusion, we have come up with a set of recommendations, the most important of which is for travel agencies to give greater importance to advertising through television and magazines to attract users of these tools. This is supported by our study, which found that a large percentage of respondents did not agree that travel agencies in Djelfa use television and magazines to advertise their offers. It is also worth noting the organization of awareness campaigns to educate consumers.